The effect of inclination and stand-off on the dynamic response of beams impacted by slugs of a granular material. (15th March 2015) - Uth, T.; Wadley, H.N.G.; Deshpande, V.S.
Abstract: The dynamic response of end-clamped sandwich and monolithic beams to impact by high-velocity tungsten carbide (WC) particle columns (slugs) has been measured with the aim of developing an understanding of the interaction of ejecta from a shallow-buried explosion with structures. The monolithic beams were made from stainless steel, while the sandwich beams of equal areal mass comprised stainless steel face sheets and an aluminium honeycomb core. High-speed imaging was used to measure the transient transverse deflection of the beams, to record the dynamic modes of deformation, and to observe the flow of the WC particles upon impact. The experiments show that sandwich beams deflect less than the monolithic beams both in normal and inclined impact situations. Moreover, the deflections of all beams in the inclined orientation were less than their respective deflections in the normal orientation at the same slug velocity. Intriguingly, the ratio of the deflection of the sandwich to monolithic beams remains approximately constant with increasing slug velocity for inclined impact but increases for normal impact; i.e. inclined sandwich beams retain their advantage over monolithic beams with increasing slug velocity. Dynamic force measurements reveal that (i) the momentum transferred from the impacting slug to both monolithic and sandwich beams is the same, and (ii) the interaction between the impacting particles and the dynamic deformation of the inclined monolithic and sandwich beams results in a momentum transfer into these beams that is equal to or greater than the momentum of the slug. These experimental findings demonstrate that contrary to intuition and widespread belief, the performance enhancement obtained from employing beam inclination is not due to a reduction in transferred momentum. Finally, we show that increasing the stand-off distance decreases beam deflections. This is because the slugs lengthen as they traverse towards their target and thus the duration of loading is extended with increasing stand-off. However, combining increased stand-off with sandwich construction does not yield the synergistic benefits of sandwich construction combined with beam inclination.